Synthesis of S-mono- and S, O-bis-1, 2, 3-triazole linked 1, 5-benzodiazepine conjugates and evaluation of their cytotoxic, anti-tyrosinase, and anti-cholinesterase activities. (3rd July 2017) - Abdallah, Wejdane; Znati, Mansour; Regazzetti, Anne; Dargère, Delphine; Laprévote, Olivier; Ben Jannet, Hichem; Gharbi, Rafik
GRAPHICAL ABSTRACT: ABSTRACT: A series of S -mono and S, O -bis-1, 2, 3-triazole linked 1, 5-benzodiazepines (BZD) conjugates6a-j and7a-j were synthesized employing "click chemistry" under microwave irradiation. The synthesized derivatives have been evaluated for their cytotoxic (MCF-7, HeLa, A549 cell lines), anti-tyrosinase and anti-cholinesterase activities. These molecules exhibited moderate to good biological activity.